EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TTW DAN TPS PADA PERSAMAAN GARIS LURUS DITINJAU DARI KARAKTERISTIK CARA BERPIKIR SISWA SMP NEGERI SE-KABUPATEN PRINGSEWU - Suningsih, Ari; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purposes of the research were to determine the effect of learning models on mathematics achievement viewed from students mindÂ style. The learning model compared were TTW (Think Talk Write), TPS (Think Pair Share) and conventional. The kind of research was a quasi experimental research. The population was the students of Junior high school in Pringsewu regency on academic year 2013/2014. The size of the sample was 286 students, consisted of 98 students in the first experimental group, 105 students in second experimental group and 84 students in control group. The instruments used were mathematics achievement test and questionnaire. Hypothesis analysis test used two ways analysis of variance with unbalanced cells. The conclusions were as follow. (1) TTW model gave the same effect as TPS, but TTW modelÂ was better than conventional and TPS model gave the same effect as conventional. (2) For all types of students mind style gave the same effect for mathematics learning achievement of students. (3) In each model of learning, students with mind style types concrete sequential, abstract sequential, concrete random, or abstract random have the same effect for mathematics learning achievement. (4) In each mind style, TTW model gave the same effect as TPS, but TTW model was better than conventional and TPS model gave the same effect as conventional.Keywords: TTW, TPS, Conventional, Mind Style, Mathematics Learning Achievement.